2001
DOI: 10.1073/pnas.091016398
|View full text |Cite
|
Sign up to set email alerts
|

Methionine adenosyltransferase 1A knockout mice are predisposed to liver injury and exhibit increased expression of genes involved in proliferation

Abstract: Liver-specific and nonliver-specific methionine adenosyltransferases (MATs) are products of two genes, MAT1A and MAT2A, respectively, that catalyze the formation of S-adenosylmethionine (AdoMet), the principal biological methyl donor. Mature liver expresses MAT1A, whereas MAT2A is expressed in extrahepatic tissues and is induced during liver growth and dedifferentiation. To examine the influence of MAT1A on hepatic growth, we studied the effects of a targeted disruption of the murine MAT1A gene. MAT1A mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
411
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(438 citation statements)
references
References 46 publications
24
411
0
3
Order By: Relevance
“…30 Furthermore, reduced expression of Gjb2 (Cx26) is known to contribute to the promotion and progression of hepatocarcinogenesis in rats. 31 Of interest, our microarray analysis unveiled the altered expression of genes involved in Wnt/b-catenin signaling; down-regulation of the Wnt antagonist Sox17 (P ¼ 0.009), up-regulation of a Wnt downstream effector Cyclin D1 (P ¼ 0.001), and modestly increased expression of the Wnt receptor Fzd7 (P ¼ 0.098).…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, reduced expression of Gjb2 (Cx26) is known to contribute to the promotion and progression of hepatocarcinogenesis in rats. 31 Of interest, our microarray analysis unveiled the altered expression of genes involved in Wnt/b-catenin signaling; down-regulation of the Wnt antagonist Sox17 (P ¼ 0.009), up-regulation of a Wnt downstream effector Cyclin D1 (P ¼ 0.001), and modestly increased expression of the Wnt receptor Fzd7 (P ¼ 0.098).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Mato and colleagues showed that MAT1A − /− mice, which are deficient in SAM, spontaneously develop steatohepatitis and hepatocellular carcinoma demonstrating that SAM depletion primes the liver for progression to more severe injury [184,185]. Mitochondria isolated from liver of MAT1A − /− mice also have decreased levels of the mitochondrial encoded subunits for cytochrome c oxidase and reduced membrane potential [186].…”
Section: Are Antioxidants Feasible Treatments For Fatty Liver Disease?mentioning
confidence: 99%
“…To more clearly interrogate the role of AdoMet in regulating CBS levels, we used the transgenic murine model in which the gene for MAT1A (encoding the MATI͞III isoenzyme) is disrupted (11). This knockout induces expression of the MATII isoenzyme in liver with a consequent lowering of hepatic AdoMet and glutathione levels by 4-and 2.5-fold, respectively, and results in an Ϸ8-fold increase in plasma methionine levels (11). Chronic hepatic insufficiency of AdoMet in the MAT1A knockout mice predisposes them to spontaneous steatohepatitis and hepatocellular carcinoma (11,12).…”
Section: Cbs Is Repressed In Mat1a Knockout Mice With High Methioninementioning
confidence: 99%